Role of Bronchoscope Utilization in Sputum AFB & Gene Xpert Negative individuals at Kathmandu Medical College Teaching Hospital - Mishra, Navin Kumar; Thakuri, Hema Chand; Shrestha, Sareen; Rai, Utshav; Dhamala, Rasmita; Nepali, Rohit; Dahal, Suresh; Sha, Parmeshwar; Khadka, Gaurav; Lamichhane, Aayush; et al. (Nepalese Respiratory Journal, 2024)
Background: Respiratory diseases are among the top most cause of mortality globally as per World Health Organization data with chronic obstructive pulmonary disease (COPD), Lung Cancer, Lower Respiratory tract infection and Tuberculosis (TB) among the top ten causes of mortality. Bronchoscope is still in growing phase in our setting despite its significant utility in establishing diagnosis and treatment of patient. Bronchoscope has pivotal role in various benign (Eosinophilic pneumonia, tuberculosis, Interstitial Lung Disease etc.) as well as Malignant (Lung Cancer) Respiratory diseases etc. Objective: To find out the efficacy of bronchoscope in detecting tuberculosis among sputum smear acid-fast bacilli (AFB) and GeneXpert negative individuals. Method: A single center, prospective, cross sectional study design was conducted which included all patients seen by Pulmonary Medicine department of Kathmandu Medical College Teaching Hospital (KMCTH). Patients were offered bronchoscopy if clinical history, examination, sputum microbiology and imaging findings demanded. Results: A total of 111 cases underwent Fiberoptic bronchoscopy (FOB) at our center during the study period for various indications. Out of which 62 (55.86%) were male and 49 (44.14%) were Female. Among a total of 45 cases with strong clinical suspicion of pulmonary tuberculosis but sputum AFB and GeneXpert-negative tuberculosis who underwent FOB, a total of 30 (66.67%) individuals were confirmed to have tuberculosis in bronchoalveolar lavage (BAL) GeneXpert, out of which 17 (56.67%) were male and 13 (43.33%) were female. Conclusion: FOB is very useful in establish diagnosis of Tuberculosis in selected patients with negative Sputum AFB and GeneXpert result.